THE ANALYSIS OF SHARIA EMITENTS IN JII CONCERNING FACTORS OF CAPITAL STRUCTURE FOR THE 2014 – 2018 PERIOD - Anisa Priyanka Jasmine; Imron Mawardi (Universitas Airlangga, 2020)
This study was made with the aim to examine the effect of profitability, company size, company age, growth opportunity, liquidity and dividend payout ratio on the capital structure of Islamic issuers listed in the JII (Jakarta Islamic Index). The method in this study uses multiple regression analysis techniques with Random Effet Model (REM) selected as the best model for estimating panel data regression, where in estimating the General Least Saquare (GLS) regression test is used. And produce profitability and dividend payout ratio as a significant variable and this also proves its effect partially on leverage (DER). While simultaneously profitability, company size, company age, liquidity and dividend payout ratio significantly influence leverage (DER).Keywords: profitability, company size, company age, growth opportunity, liquidity, dividend payout ratio, pecking order theory, capital structureREFFERENCE Ahmad, Rodoni dan Herni, Ali. (2010). Manajemen keuangan. Jakarta: Penerbit Mitra Wacana Media.Arief, Bramantyo. (2011). Analissis pengujian teori pecking order melalui keterkaitan profitabilitas, struktuk asset, ukuran perusahaan dan kesempatan bertumbuh terhadap financial leverage periode 2006-2009 (Studi kasus pada emiten syariah di JII). Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Chen et al. (2011). How the pecking order theory explain capital structure. International Journal of Management Studies, 1-9.Darminto dan Manurung, Adler Haymans. (2008). Pengujian teori trade-off dan pecking order dengan satu model dinamis pada perusahaan publik di Indonesia. Jurnal Manajemen Bisnis, 1(1), 35-52.Dimitri, Michael dan Sumani. (2013). Analisis pengaruh likuiditas, profitabilitas, ukuran, usia, dan pertumbuhan perusahaan terhadap struktur modal. Jurnal Manajemen. 11(1), 82-105.Eviani, Anantia Devi. (2015). Pengaruh struktur aktiva, pertumbuhan penjualan, dividen payout ratio, likuiditas, dan profitabilitas terhadap struktur modal.Jurnal Akuntansi dan Sistem Teknologi Informasi, 11(2), 194 – 202.Ghozali, I (2011). Aplikasi analisis multivariate dengan program SPSS. Semarang: Universitas Diponegoro.Gujarati. Damodar N and porter Dawn C. (2009). Basic econometrics, fifth edition. New York: McGraw-Hill Irwin.Hasan and Safdar (2005). Impact of ownership structure and corporate governance on capital structure of Pakistani llisted companies. International Journal of Business & Management, 4(2).Liu. Yuanxin & Ning. Xiangbo. (2009). Empirical research of the capital structure influencing factor of electric power listed companies. International Journal of Marketing Studies, 1(1), 43-49. DOI:10.5539/ijms.v1n1p43Mau, Jefrianus, dkk. (2015). Pengaruh profitabilitas, umur dan ukuran perusahaan terhadap struktur modal. Jurnal Riset Akuntansi dan Keuangan, 11(2), 147-156.Myers. C Stewart. (1984). The Capital Stucture Puzzle. The Journal of Finance, 39(3), 575-592.Myers , S and Majluf. (1984). Corporate financing and investment decision when firms have information investors do not have. Journal of Financial Economics, 13(2), 187-221.Rahman Hakim, Arief. (2013). Pengaruh struktur aktiva, Profitabilitas, ukuran perusahaan dan likuiditas terhadap struktur modal (studi kasus pada perusahaan makanan dan minuman yang terdatar di Bursa Efek Indonesia. Skripsi tidak diterbitkan. Jakarta: Universitas Islam Negeri Syarif Hidayatullah.Dewi, Sofia Prima dan Keni Keni. (2013). Pengaruh Umur Perusahaan, Profitabilitas, Ukuran Perusahaan, dan Leverage terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan. Jurnal Bisnis dan Akuntansi, 15(1), 1-12. DOI: https://doi.org/10.34208/jba.v15i1.203